A Unit of Homemaking: The Prefabricated Panel and Domestic Architecture in the Late Soviet Union. Issue 1 (28th September 2020) - Malaia, Kateryna
This article investigates the role of an iconic Soviet material — the concrete prefabricated panel — in the making of late-Soviet urban residential architecture. The dominance of the prefabricated panel became possible due to the economic system that sustained its production and use, yet the same economic context also drove the architectural profession and the construction industry into stagnation in the 1970s and 1980s. With the help of archival and legal materials, interviews collected in Kyiv and Lviv, Ukraine, professional magazines, and through the object-based history of this basic material unit, this paper reconsiders the traditional notion of professional designers' dominant role in architectural decision-making, and highlights economic and institutional inertia in the creation of late-Soviet residential architecture. The prefabricated panel was first introduced to the USSR at the beginning of Khrushchev's ambitious and far-reaching housing campaign of the late 1950s to solve a severe housing crisis with cheap and fast experimental construction. In the 1950s and '60s, the prefabricated panel propelled innovation in the production of ordinary architecture, as well as changes in the architectural profession. However, over the next couple of decades it became the main building block in the system, one that both hampered and heavily limited residential design practices and the resulting built environment. After the dissolution of the USSR, prefabricated panels ceased to be the primary determinant in apartment building, yet panel buildings remained, once again indicating the persistence of a material building block over the political or economic system that enabled its creation.